Rethinking some mechanisms invoked to explain translational regulation in eukaryotes. - Kozak, M. (Gene, 2006)
Real progress in understanding translational regulatory mechanisms lags behind the claims of progress. Novel mechanisms were proclaimed in recent months for some important regulatory proteins from Drosophila (e.g. Bruno, Sex-lethal, Reaper), but the evidence is thin. Many flaws in the design and interpretation of new experiments can be traced to older experiments which came to be accepted, not because the evidence was overwhelming, but because the ideas were appealing. Two of these classic examples of translational regulation are discussed before taking up the newer findings. One paradigm concerns regulation of 15-lipoxygenase production during reticulocyte maturation. The mechanism postulated for 15-lipoxygenase was pieced together in vitro and has never been linked in a meaningful way to what happens naturally in reticulocytes; nevertheless, these experiments have guided (or misguided) thinking about how sequences near the 3' end of an mRNA might regulate translation. The second paradigm concerns the regulation of cyclin B1 translation in Xenopus oocytes by a protein called Maskin, which purportedly interacts with initiation factors. A third topic discussed in some detail concerns the idea that in eukaryotes, as in prokaryotes, initiation of translation might involve base-pairing between mRNA and ribosomal RNA. Recent experiments undertaken to test this idea in yeast are far from conclusive. Many of the experimental defects brought to light in this review are simple-absence of controls, reliance on indirect tests, failure to test a new test system before using it; these things are fixable. Special problems are posed by the practice of using internal ribosome entry sequences (IRESs) as tools to figure out how translation might be regulated by other components. Unanswered questions about the IRESs themselves have to be resolved before they can be used confidently as tools.